PENGARUH MEDIA PEMBELAJARAN WEB WORDWALL TERHADAP HASIL BELAJAR SISWA PADA MATERI TERMOKIMIA DI SMA KOSGORO TOMOHON - Assa, Christiano; Gugule, Sanusi (Chemistry Department, Universitas Negeri Manado, 2025)
A study has been conducted on the influence of web-based learning media Wordwall on student learning outcomes in thermochemistry material at SMA Kosgoro Tomohon. The research method used is Pretest-Posttest Control Group Design, involving 15 students of class XI A as the experimental class and 15 students of class XI B as the control class, while the t-test is carried out. Wordwall media is applied in the learning process to improve student understanding and involvement interactively in the experimental class. Based on the results of the study and discussion, it shows that the use of Wordwall has an effect on student learning outcomes, as shown through the research data, namely the average value of the experimental class of 76.19 is higher than the control class with an average of 65.96 and continued with a t-test with the help of SPSS software, a significance level value of 0.012 <α (0.05) was obtained. Therefore, this study shows a significant influence between Wordwall web media on student learning outcomes in thermochemistry material at SMA Kosgoro Tomohon. Therefore, Wordwall learning media is recommended as an innovative alternative to support the learning of complex chemical materials such as thermochemistry.